The Influence of Extremely Low Frequency (ELF) Waves for Pasteurization of Cow Milk - Saleh, Anang Supriadi; Wibisono, Yossi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The extremely low frequency (ELF) magnetic field exposure technology for food processing and preservation is a future technology that produces better food quality. This research aims to examine the exposure of extremely low frequency (ELF) magnetic field waves to pasteurized cow milk and its effect on pH, chemical content, total microbial count, and sensory tests. This research was carried out by exposing ELF waves of 834.8 micro Tesla (μT) for 90 minutes to fresh milk and pasteurized milk. Samples were stored at room temperature then observed at 0, 2, 6, and 21 hours. Each treatment was repeated three times. The results showed that exposure to ELF waves had no effect on chemical content (P<0.05). The pH measurement shows that exposure to ELF waves could maintain the pH value. The total microbial count showed that exposure to ELF waves had an effect on reducing the total microbial count. The organoleptic test showed that pasteurized milk exposed to ELF waves had a smaller level of change. Based on observations, exposure to ELF waves has the potential to be developed in pasteurization, storage of cow milk, and retain its nutritional content. Keywords: Cow milk, Exposure, Extremely low frequency, Influence, Pasteurization.